(untitled) (American Journal of Technology and Applied Sciences, 2024)
This article explores recent advances in fabrication techniques for silicon-based epitaxial p-n junctions, focusing on the role of molecular beam epitaxy (MBE), chemical vapor deposition (CVD), and atomic layer deposition (ALD). These techniques allow for precise control of doping concentrations, layer thicknesses, and interface quality, leading to improved thermoelectric efficiency. Additionally, the article discusses the challenges of minimizing thermal conductivity while maximizing electrical conductivity, aiming to optimize the thermoelectric figure of merit (ZT).